JEJAK PEMIKIRAN KOSMOPOLITAN GUS DUR: ANTARA UNIVERSALITAS ISLAM DAN PARTIKULARITAS KEARIFAN LOKAL - M. Nur Fauzi (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2019)
This paper tries to explore the basic of cosmopolitant thinking of Abdurrahman Wahid or better known as Gus Dur. Abdurrahman Wahid’s thinking has a holistic spectrum, for example the relation between Islam and democracy, religion and the state, economic people movement, struggle for human rights and anti-violence, struggle for the existence of nation state and except the Pancasila as the guidence of the plural and multicultural Indonesian society. From his several idea’s and concepts above, actually can’t be separated from Islamic universality and local wisdom particularity around society. Religious style of Indonesia has its own peculiarities. It appears on the different shades of Islamic archipelago from other coutries in the Middle East. It deals with the uniqueness of the treasures of the experience and practice of the Indonesian as their adherents. Due to the historical background of the existence of cultural experiences and religious belief of its predecessors from the different shades between Islam Indonesia and Islam from other countries existed. In carrying out Islam, they always maintain its normative religious values based on al-Qur’an and al-Hadith. In addition they also carry out historical teachings, in wich the role of spiritual values, inner values (esoteric) in religion, especially the values of human morality has become a very urgent principle in his life. As religion that carry out a mission of universal humanity, Islam must be adapted with any cultural and local wisdom in the world. The universal principles of Islam, for the example equality, openes attitude, brotherhoods, love each other, peacefull, justice, sovereignity of law, and respectfully each others, was cosmopolitant civilization values of Islam. From this research, founded that the basic of cosmopolitant thinking Gus Dur has clearly and fix references. From this starting point Gus Dur tried to spread it on nationally and globally. Clearly, Islam within, was inherent with universality and particularity values.